Job Satisfaction, Work Values and Stress in University Teachers - Pociūtė, Birutė; Bulotaitė, Laima; Bliumas, Remigijus (Acta Paedagogica Vilnensia, 2012)
The development of higher education changes the performance of universities as well as the roles and influences of academic staff. Modern research of teachers’ stress usually emphasizes the prevalence and intensity of stress in the community of universities. The objective of this study was to assess job satisfaction and stress features, stress coping strategies, also relations of these variables to work values in university teachers. The results revealed the job satisfaction in university academic staff and significant relations between stress in various academic areas of work and job satisfaction. The study has revealed that teachers give priority to values such as altruism, autonomy, achievement. Important differences between young teachers and their senior colleagues in work values such as comfort and altruism have been also found. Young teachers are critical to the wage system, to the level of fees in particular. Teachers who give priority to the values of academic work and often experience stress at work tend to use a rational strategy for stress coping. This coping strategy is positively correlated with job satisfaction, while emotional stress coping strategy and work values are correlated negatively.